The drivers of energy efficiency improvement among nine selected West African countries: A two-stage DEA methodology - Francis Atta Sarpong; Jianmin Wang; Benjamin Blandful Cobbinah; Jesse Jackson Makwetta; Jie Chen (Energy Strategy Reviews, 2022)
There has been a general outcry globally to ensure sustainable environmental practices by minimizing CO2 while increasing economic growth. In general, most African countries have had the lowest energy efficiency levels over the past decades. This is because of higher inefficiency due to mismatches between efficiency inputs and outputs. Previous studies have only focused on measuring the energy efficiency of African countries without determining the drivers of such efficiency. Hence, the current study adopted the two-stage Data Envelopment Analysis (DEA) methodology to measure energy efficiency among nine selected West African states and their influencing factors. The focus of the first-stage DEA was to measure the energy efficiency among the nine selected countries using the Dynamic Slack Based Measure (SBM) DEA model with and without the inclusion of CO2 emissions and the Malmquist Productivity Index (MPI) to estimate the technology efficiency improvement. Panel data from 2007 to 2020 was used for the study. The study found that energy efficiency without the inclusion of CO2 emissions in West Africa has improved during the period ranging from 2007 to 2020. Of the nine countries involved in the study, four of them, including Ghana, Nigeria, Côte d'Ivoire and Senegal, had an efficiency level above 100% with an average economic growth of 6% during the sampled period of the study. The efficiency level increased with an 6% increase in economic growth and a reduction in CO2 emissions. The Tobit regression model was adopted in stage two to analyze the factors that may affect energy efficiency in West Africa. The study results revealed a significant and positive association between population and energy efficiency in West Africa. At the same time, gross national income and urbanization negatively influence West Africa's energy efficiency. The findings were in line with the results from the fixed effect estimates. The study concludes that despite the improvement in energy efficiency in West Africa, there is a need to further boost their efficiency by reducing carbon dioxide emissions and other harmful pollutants. According to the study, West African leaders should adapt global benchmarks of sustainable environmental practices for sustainable energy implementation for the sustainable energy sector.